Expression and significance of CEMIP and CYP11B2 in serum in women with foetal growth restriction - Yang Yue; Fang Fang Zhou; Jia Rong Zhang; Fu Xu (Journal of Obstetrics and Gynaecology)
Background Foetal growth restriction (FGR) occurs when a foetus fails to reach its growth potential. This observational study assessed the expression and significance of cell migration-including protein (CEMIP) and aldosterone synthase (CYP11B2) in the serum of pregnant women with FGR.Methods 40 singleton FGR-suffered pregnant women, as well as 40 normal singleton pregnant women, were enrolled. The expression of CEMIP and CYP11B2 in serum was detected in early pregnancy. The correlations between parameters were evaluated. The predictive variables for FGR were determined. The diagnostic value of CEMIP and CYP11B2 for FGR was analysed.Results CEMIP and CYP11B2 mRNA expression in the serum of pregnant women with FGR decreased (both P < 0.001). CEMIP (95%CI: 0.802–0.921, P < 0.001) and CYP11B2 (95%CI: 0.795–0.907, P < 0.001) mRNA expression in serum and soluble fms like tyrosine kinase-1 (sFLT1)/placental growth factor (PlGF) ratio (95%CI: 0.866–0.974, P < 0.001) were independent predictors of FGR, and CEMIP (r = −0.578, P = 0.001) and CYP11B2 (r = −0.602, P < 0.001) mRNA expression in serum were negatively correlated with sFLT1/PlGF ratio. CEMIP (AUC = 0.741) and CYP11B2 (AUC = 0.764) mRNA expression in serum had good diagnostic value for FGR.Conclusion The expression of CEMIP and CYP11B2 is reduced in the serum of pregnant women with FGR and may become new diagnostic markers for FGR.